Optical coherence tomography for use in infrared laser sealing of blood vessels - Giglio, Nicholas C. (IEEE Photonics Conf, 2020)
Infrared lasers may provide faster sealing of vascular tissues with less collateral thermal damage and lower device temperatures than radiofrequency and ultrasonic devices currently used for surgery. Optical coherence tomography is tested to image native and thermally coagulated blood vessels, as a potential feedback system.